The validity and reliability of 1-Hz and 5-Hz global positioning systems for linear, multidirectional, and soccer-specific activities - Portas, M. D.; Harley, J. A.; Barnes, C. A.; Rush, C. J. (International Journal of Sports Physiology and Performance, 2010)
Purpose: The study aimed to analyze the validity and reliability of commercially available nondifferential Global Positioning System (NdGPS) devices for measures of total distance during linear, multidirectional and soccer-specific motion at 1-Hz and 5-Hz sampling frequencies. Methods: Linear (32 trials), multidirectional (192 trials) and soccer-specific courses (40 trials) were created to test the validity (mean ± 90% confidence intervals), reliability (mean ± 90% confidence intervals) and bias (mean ± 90% confidence intervals) of the NdGPS devices against measured distance. Standard error of the estimate established validity, reliability was determined using typical error and percentage bias was established. Results: The 1-Hz and 5-Hz data ranged from 1.3% ± 0.76 to 3.1% ± 1.37 for validity and 2.03% ± 1.31 to 5.31% ± 1.2 for reliability for measures of linear and soccer-specific motion. For multidirectional activity, data ranged from 1.8% ± 0.8 to 6.88% ± 2.99 for validity and from 3.08% ± 1.34 to 7.71% ± 1.65 for reliability. The 1-Hz underestimated some complex courses by up to 11%. Conclusions: 1-Hz and 5-Hz NdGPS could be used to quantify distance in soccer and similar field-based team sports. Both 1-Hz and 5-Hz have a threshold beyond which reliability is compromised. 1-Hz also underestimates distance and is less valid in more complex courses.